Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF

Synthesis and characterization of microwave-hydrothermally derived Ba1-xSrxTiO3 powders - Deshpande, S. B.; Khollam, Y. B.; Bhoraskar, Y. B.; Date, Sadgopal K.; Sainkara, S. R.; Potdar, H. S. (Materials Letters, 2005)
Submicron-sized, spherical, stoichiometric strontium substituted barium titanate: Ba0.75Sr0.25TiO3 (BST) powders are prepared by microwave-hydrothermal (MH) route under the MH conditions of 200 degreesC, 200 psi, and 30 min in strongly alkaline conditions (pH>12) using potassium titanyl oxalate (KTO) and nitrates of Ba and Sr as the starting precursors and KOH as the mineralizer. The characterization studies by XRD, XRF and SEM indicated that stoichiometric cubic BST powders (a(0)=3.992 A) were obtained by adjusting MH conditions mentioned earlier and keeping the (Ba+Sr)/Ti ratio in starting solution slightly in excess (similar to1.06). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; dissolution-recrystallization; Microstructure; microwave-hydrothermal synthesis; mineralizer; SEM; XRD; XRF

Synthesis of star shaped Ba1-xSrTiO3 (BST) powders - Khollam, Y. B.; Potdar, H. S.; Deshpande, S. B.; Gaikwad, A. B. (Materials Chemistry and Physics, 2006)
Uniform star shaped strontium substituted barium titanyl oxalate Ba1-xSrxTiO(C2O4)(2) (BSTO)/strontium substituted barium titanate, Ba1-xSrxTiO3 (BST) powders were prepared via a simple chemical co-precipitation route with x = 0.15, 0.20, and 0.25. The process involved an addition of 0.1 M solution of titanium tetrabutoxide (BTM) in isopropanol (IPA) to 0.1 M oxalic acid in IPA containing 0.2 M of H2O to produce titanyl oxalate precipitate which was further reacted with 0.1 M solution of ammonium oxalate to obtain 0.1 M clear homogeneous solution of ammonium titanyl oxalate (ATO) with pH 4.25 containing titanium in the form of soluble anionic oxalate species [TiO(C2O4)(2)(2-)]. Stoichiometric quantities of barium hydroxide and strontium nitrate were dissolved in distilled water and its pH was adjusted nearly equal to that of ATO (similar to 4.15) by drop wise addition of dilute HNO3 solution 1:10 (v/v). The addition of this mixed cation precursor solution to ATO solution resulted in precipitation of strontium substituted barium titanyl oxalate (BSTO) having star shaped morphology. The calcination of BSTO precursors at 730 degrees C for 4 h in air produced cubic BST powders (a(o) similar to 4.001, 3.996 and 3.991 angstrom for x = 0. 15, 0.20, 0.25, respectively) having star shaped morphology. SEM, XRD and IFTIR techniques were used to characterize the BSTO/BST powders. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; capping agent; Co-precipitation; Morphology

Synthesis of bismuth titanate (Bi4Ti3O12)powders via calcination of microwave-hydrothermally (MH) derived precursor - Khollam, Y. B.; Deshpande, S. B.; Samuel, V.; Potdar, H. S. (Indian Journal of Engineering and Materials Sciences, 2008)
Micrometer sized platelet-like particles of bismuth titanate (Bi4Ti3O12) ire prepared successfully by the calcination of a mixed-precursor in air. The mixed precursor is precipitated Under microwave-hydrothermal (MH) treatment via dissolution-recrystallization kinetics. The mixed precursor is precipitated in-situ by giving MH treatment (at 200 degrees C, 200 psi, and 30 min hold time) to the hydrolysed slurry containing Bi and Ti cations. The slurry was prepared by adding 20% aqueous KOH precipitant solution to a well-mixed stoichiometric nitrate solution containing Bi and Ti cations. XRD results revealed that the as-dried precursor consisted of a homogenous mixture of non-crystalline particles of Bi2O3 and TiO2. The calcination of the as-dried precursor at 700 degrees C/2 h in air resulted ill the formation of micron sized platelet like single-phase Bi4Ti3O12 powders having orthorhombic structure.
Keywords: Bi4Ti3O12; MH processing; SEM; XRD

Simple chemical co-precipitation/calcination route for the synthesis of simulated synroc-B and synroc-C powders - Potdar, H. S.; Vijayanand, S.; Mohaideen, Kamal Khaja; Patil, K. R.; Joy, Pattayil Alias; Madhavan, R. Raja; Kutty, K. V. G.; Ambashta, Ritu D.; Wattal, P. K. (Materials Chemistry and Physics, 2010)
A simple chemical co-precipitation/calcination route was developed for the synthesis of simulated synroc-B and synroc-C powders using mostly nitrate salts as starting chemicals and 20% ammonia solution as precipitant. In this route, a mixed solution containing Al-nitrate, Ca-nitrate, Ba-nitrate, zirconyl nitrate and titanyl nitrate in the molar proportion required for synroc-B is added to dilute ammonia solution to precipitate these cations in the form of their hydroxides at room temperature by maintaining pH approximate to 10.5 during precipitation. Formation of a major fluorite phase with minor amounts of anatase, rutile and hollandite phases is observed in the powder obtained after calcination in air at 750 degrees C. Multiphase crystalline synroc-B matrix containing hollandite, perovskite, zirconolite, and rutile phases is obtained after sintering the heat treated powder in the form of pellets at 1230 degrees C for 4h in air. Similarly, pure synroc-C phases with 14 and 20% simulated waste loadings were synthesized following the same synthesis protocol. These pre-treated powders with a high surface area of similar to 25 m(2) g(-1) gave sintered ceramics having density of similar to 90% for 14 and 20% waste loadings. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Oxides; Sintering